IMPLEMENTASI HOTSPOT LOGIN MENGGUNAKAN CAPSMAN MIKROTIK PADA WILAYAH YANG BERBEDA - Tommy Alfian Armawan Sandi; Eka Kusuma Pratama; Ilham Nur Leksono; Rian Septian Anwar (Jurnal Akrab Juara, 2019)
The development of wireless technology is currently so fast, every communication device such as smartphones, tablets, and portable computers supports the wireless technology. It's no stranger when somewhere provides wireless networks especially if the wireless network is connected to the internet network. If the wireless network has been formed then the next problem is how the network can cover all areas or places that exist, then what about the security system, whether the wireless network is already safe than the stylists. Then, whether the administrator can look at controlling the activities of users, and what if there are two or more places with different areas but want to make the administrator centrally. By using CAPsMAN which is synergized with Userman and Radius Server using the Extended Service Set topology and connecting between regions via VPN, this wireless network will be controlled, monitored and configured centrally, bringing Authentication, Authorized and Accounting features in userman to make the network usable using an account By itself, using a VPN for interconnection ensures that account usage can be done using the same account, and applying an extended service set topology can produce a stable network without interrupted interruptions.